The use of the Eurosystem's monetary policy instruments and its monetary policy implementation framework in 2022 and 2023 - Tom Hudepohl; Suzanne Malderez (European Central Bank (ECB), 2024)
The Eurosystem implements its monetary policy through a set of monetary policy instruments (MPIs). The period covered by this report (2022-23) was dominated by high inflation, which led to a change from an easing to a tightening monetary policy environment in line with the mandate of the European Central Bank (ECB) to pursue price stability. This report focuses on the accompanying shift in the use of MPIs. Key ECB interest rates were hiked to an unprecedented extent and at exceptional speed, leading to an exit from negative interest rates. This was accompanied by a gradual phasing-out of reinvestments under the asset purchase programmes, revisions to the conditions of targeted longer-term refinancing operations (TLTROs) and their subsequent substantial early repayments, and a phasing-out of pandemic collateral easing measures. This report discusses these developments and provides a full overview of the Eurosystem's monetary policy implementation from 2022-23.
Keywords: D02; E43; E58; E65; G01; 330; monetary policy implementation; refinancing operations; asset purchase programmes; central bank counterparty framework; central bank collateral framework; central bank liquidity management; non-standard monetary policy measures